PROTECTIVE EFFECT OF LIV.52 AGAINST ACETAMINOPHEN INDUCED TOXICITY IN WISTAR RATS - D.P.SANTHOSH KUMAR,; M.DEECARAMAN,; M.VIJAYALAKSMI,; RAMESH EDAMULA,; H.KRISHNAPPA, (International Journal of Pharma and Bio Sciences, 2015)
The present study was carried out with the objective to assess the protective effect of Liv.52 on acetaminophen induced hepatotoxicity will also protect its toxic effects in Wistar rats when administered orally for 14 consecutive days. Acetaminophen induced toxicity was evaluated by administering daily doses of 750 or 1500 mg/kg/day through oral gavage. The treatment resulted in clinical signs and decreased body weights and food intake in association with hepatic and renal toxicity in acetaminophen treated group at 1500 mg/kg/day. However, all these toxicological effects were found to be reversible when Liv.52 at 1000 mg/kg/day was co-administered with acetaminophen at 1500 mg/kg/day. The treatment with acetaminophen alone at 750 mg/kg/day or Liv.52 alone at 1000 mg/kg/day or co-administration of test items (Liv.52 at 1000 mg/kg/day+acetaminophen at 750 mg/kg/day) did not induce any toxicological effects. In summary, Liv.52 an herbal formulation has shown a significant protection against acetaminophen induced toxicity in Wistar rats.